2014
DOI: 10.1007/s11368-014-0938-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of visible and near-infrared reflectance measurements for identifying the source of suspended sediment in rivers and comparison with geochemical fingerprinting

Abstract: Purpose -Visible and near-infrared (Vis-NIR) reflectance measurements may be an alternative technique to identify suspended sediment sources in streams of headwater catchments. In this study, we examined if Vis-NIR reflectance measurements are capable of estimating sediment source contribution to sediment yield and compared this technique with the chemical technique.Materials and methods -Two headwater catchments in Ethiopia, Unta (2052 ha) and Desera (1657 ha), were both analyzed with the same techniques in o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 43 publications
(58 reference statements)
0
22
0
Order By: Relevance
“…However, it can make the fingerprinting exercise highly laborintensive and costly, constraining the adoption of the procedure as a management tool to estimate sediment origin. In this regard, several studies have been carried out in the last years suggesting the use of visible reflectance and color parameters as a rapid and cheap means for investigating sediment sources (Martínez-Carreras et al, 2010a, 2010b, 2010cLegout et al, 2013;Verheyen et al 2014). A UV-VIS spectrometer is a very affordable equipment used in a wide range of science fields (e.g., chemistry, pharmacology, plant physiology, food science, soil science, etc.…”
Section: Source Apportionmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it can make the fingerprinting exercise highly laborintensive and costly, constraining the adoption of the procedure as a management tool to estimate sediment origin. In this regard, several studies have been carried out in the last years suggesting the use of visible reflectance and color parameters as a rapid and cheap means for investigating sediment sources (Martínez-Carreras et al, 2010a, 2010b, 2010cLegout et al, 2013;Verheyen et al 2014). A UV-VIS spectrometer is a very affordable equipment used in a wide range of science fields (e.g., chemistry, pharmacology, plant physiology, food science, soil science, etc.…”
Section: Source Apportionmentmentioning
confidence: 99%
“…More recently, MIR (Poulenard et al, 2009(Poulenard et al, , 2012Evrard et al, 2013) and VIS-NIR (Martínez-Carreras et al, 2010a,b;Legout et al, 2013;Brosinsky et al, 2014a,b;Verheyen et al 2014;Tiecher et al, 2015) spectroscopy has also been applied to trace suspended sediment origin. The prerequisites for use of tracer properties in sediment fingerprinting studies are the conservativeness and the linear additive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Visible (VIS) and near‐infrared (NIR) reflectance was tested in the French Alps (Legout et al , ), Luxemburg (Martínez‐Carreras et al , , , ), Spain (Brosinsky et al , , ), Ethiopia (Verheyen et al , ), the Eastern Cape of South Africa (Pulley and Rowntree, ), United Kingdom (Collins et al , ) and Southern Brazil (Tiecher et al , , ). Besides, some of these studies showed a good agreement between the results obtained with the spectroscopic method and those provided by the conventional fingerprinting approach based on geochemical properties (Martínez‐Carreras et al , ; Legout et al , ; Verheyen et al , ; Tiecher et al , , ). Near‐infrared spectroscopy have proved to be a valuable tool to trace sediment originating from different land uses [e.g., badland and forest/grassland – Brosinsky et al .…”
Section: Introductionmentioning
confidence: 99%
“…(, ); landslide, cropland, adnd grazing land –Verheyen et al . (); cropland, unpaved road and stream channels – Tiecher et al . ()], parent material [black marls, limestones and molasses – Legout et al .…”
Section: Introductionmentioning
confidence: 99%
“…However, bands near 4500 cm À1 can also be characteristic of AlOeH bending and OeH stretching of clay minerals such as kaolinite and gibbsite (Verheyen et al, 2014).…”
Section: Diffuse Reflectance Infrared Fourier Transform Spectroscopy mentioning
confidence: 99%